An Examination of the Professional Characteristics of Management: Rectors of Foundation Universities in Turkey (Third Sector Social Economic Review, 2026)
This study aims to raise awareness of management as a profession and to examine whether rectors of foundation (non-profit private) universities in Turkey meet the profession’s key educational and qualification criteria. The population includes all 74 foundation universities (N = 74), state universities are excluded due to different governance. Rectors’ degree fields (BA/MA/PhD), graduation years, professorship year, rector tenure, and managerial experience were compiled from public sources (YÖK Academic, the YÖK Thesis Center, university websites, and LinkedIn). “Professional management” was operationalized using ISCO-08 (unit group 1120; skill level 4) and ISCED-F 2013 field 0413, and contrasted with Turkey’s National Qualifications Database (ILO, 2012; UNESCO, 2015; Republic of Türkiye Ministry of Labour and Social Security, 2025). Data were analyzed with descriptive statistics in SPSS 19 and Microsoft Excel. Results show that 88% of rectors lack ISCED-F qualifications and 77% lack management credentials in the national database; thus, over 75% of foundation universities are not led by professional managers. Most rectors are men (85%); while 73% have ≥10 years of total managerial experience, only 12% have ≥10 years of rector tenure.
Keywords: Management; Management as a Profession; Manager; Profession; Rectors